Modelowanie procesów biznesowych z wykorzystaniem logiki domniemań - Kędzierski, Stanisław (Defeasible logic in business process modelling, 2005)
There are many models of organization. Business process is one of components of enterprise model. Business process can be presented in many ways: non-formal, semiformal or formal. Formal methods are very interesting for their character especially for precisely modelling of business processes. Human actors perform business process. Defeasible logic is a suitable tool for modeling human behavior. Paper present an application of defeasible logic to modeling a simple process of buying a second hand car.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 97-107